microRNA Fine-Tuning of the Germinal Center Response - Fuertes, Teresa; Salgado, Irene; de Yébenes, Virginia G. (Frontiers in Immunology, 2021)
Germinal centers (GCs) are complex multicellular structures in which antigen-specific B cells undergo the molecular remodeling that enables the generation of high-affinity antibodies and the differentiation programs that lead to the generation of plasma–antibody-secreting cells and memory B cells. These reactions are tightly controlled by a variety of mechanisms, including the post-transcriptional control of gene expression by microRNAs (miRNAs). Through the development of animal models with B cell-specific modified miRNA expression, we have contributed to the understanding of the role of miRNAs in the regulation of GC responses and in B cell neoplasia. Here, we review recent advances in the understanding of the role of miRNAs in the regulation of B cell and T follicular helper physiology during the GC response and in the diseases associated to GC response dysregulation.